BOD as a Measure of Fluvial Organic Matter Lability—The Decoupling of O2 Consumption From CO2 Production. Issue 12 (8th December 2021) - Worrall, Fred; Howden, Nicholas J. K.; Burt, Tim P.
Abstract: Biochemical oxygen demand (BOD) has been taken as a measure of the lability of the fluvial organic matter (both dissolved and particulate organic matter—DOM and POM), but such a link is based on a number of assumptions. First, the oxidation state of the organic carbon is zero and the molar stoichiometry of the reaction between organic C and O2 is 1. Second, the consumption of O2, as measured by BOD, is a first‐order reaction with respect to DOM or POM. Third, that POM and DOM are correlated. Applying a Bayesian hierarchical analysis to an extensive river monitoring records for 236 sites across Great Britain from 1974 to 2019, it is possible to test the nature of the link between BOD and fluvial organic matter. The study shows that: (a) The inclusion of both DOC and SS concentrations improved the modeling. (b) When a first‐order reaction was assumed there was no significant linear relationship with BOD and DOC and suspended solids (SS) in at least 98% of cases. (c) 53% of sites showed a zero‐order reaction; when there was a significant order of reaction, the median was 0.28 and was never larger than 0.93, that is, a first‐order reaction rate was never observed. The lack of significant relationship means that the supply of organic matter exceeds the capacity to turn over that organic matter; and that given the range of oxidation states of fluvial organic carbon, it is possible to completely decouple O2 consumption from fluvial organic matter concentration in rivers. Key Points: Study tests assumptions about the link between BOD and DOC in rivers across 236 sites and 45 years of data Majority of rivers show a zero‐order reaction between BOD and DOC implying that rivers are capacity‐ and not supply‐limited Study shows decoupling of O2 consumption from fluvial organic matter in UK rivers